Respuesta :

Answer:

Let the first number be

[tex]=x[/tex]

Let the second number be

[tex]=y[/tex]

The sum of two numbers is 83 can be represented below as

[tex]x+y=83\ldots\ldots(1)[/tex]

The difference of the 2 numbers is 13 can be represented below as

[tex]x-y=13\ldots\ldots\text{.}(2)[/tex]

Step 1:

From equation (1) make x the subject of the formula to to give equation (3)

[tex]\begin{gathered} x+y=83\ldots\ldots(1) \\ x=83-y\ldots\text{.}(3) \end{gathered}[/tex]

Step 2:

Substitute equation (3) in equation (2)

[tex]\begin{gathered} x-y=13\ldots\ldots\text{.}(2) \\ x=83-y\ldots\text{.}(3) \\ 83-y-y=13 \\ 83-2y=13 \\ \text{collect similar terms,} \\ -2y=13-83 \\ -2y=-70 \\ \text{divide both sides by -2} \\ \frac{-2y}{-2}=\frac{-70}{-2} \\ y=35 \end{gathered}[/tex]

Step 3:

Substitute y= 35 in equation (3)

[tex]\begin{gathered} x=83-y\ldots\text{.}(3) \\ x=83-35 \\ x=48 \end{gathered}[/tex]

Hence,

The product of the two numbers will be calculated as

[tex]\begin{gathered} =x\times y \\ =35\times48 \\ =1680 \end{gathered}[/tex]

Hence,

The final answer is = 1680

OPTION D is the final answer